Analysis of a double nonlinear parabolic crosswise-diffusion system: Analysis of a double nonlinear parabolic crosswise-diffusion system - Bobokandov, Makhmud (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Annotation. Our main goal in this research is to investigate the characteristics of self-similar solutions to the Cauchy problem. Specifically, we analyse the behaviour of these solutions in a source in a nonhomogenous medium and in a double nonlinear time-dependent parabolic system of equations. We investigate the self-similar analysis of the solutions, allowing us to establish the global solvability conditions of the Cauchy problem of the Fujita type.